PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN USAHA MAKANAN TRADISIONAL DI BALI - Pande Ketut Ribek; Luh Putri Mas Mirayani; Yenny Verawati; Ni Putu Chintya Pradnyandari; Nyoman Agus Chandra Sekharendra (Lembaga Penelitian dan Pengabdian Masyarakat (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2023)
This research aims to determine the influence of organizational commitment, organizational culture and job satisfaction on the performance of employees of traditional food businesses in Bali. The population in this study were all traditional food businesses in Bali. The sample was determined using a saturated sampling technique with a sample size of 35 business owners. Data collection methods include observation, interviews, documentation and questionnaires. The data analysis technique used is multiple linear regression analysis. SPSS The test results show that organizational commitment has a positive and significant effect on the performance of traditional food business employees in Bali. Organizational culture has a positive and significant effect on the performance of employees of traditional food businesses in Bali. and job satisfaction has a positive and significant effect on employee performance in traditional food businesses in Bali. The better the organizational commitment, organizational culture and employee satisfaction, the greater the employee performance in traditional food businesses in Bali.